EVALUASI PERLINTASAN SEBIDANG NO 337 KM 157+846 ANTARA BRAMBANAN – MAGUWO - Pinta Prasetya (Bajang Institute, 2025)
Accessibility and movement generation will create traffic flow, one of which is at Level Crossings. Based on KAI Daop Yogyakarta data, in the 2022-2024 period there have been 34 accidents at level crossings in the KAI Daop 6 Yogyakarta area. So it is necessary to handle safety at railway crossings more intensively in a measured and well-measured manner. As for. The purpose of this study is to analyze and evaluate at level crossings, compliance with regulations, and provide recommendations for handling. This study uses a library study method and primary data collection. Primary data consists of comparative data on existing conditions with technical standards, both road section construction at Level Crossings with the research location on the crossing route (JPL) No. 337 Km 157 + 846 between Brambanan - Maguwo. The results of the study indicate that the existing condition of road equipment facilities and geometrics are not fully in accordance with regulations. The geometric condition of the highway with a slope of 12%. This could potentially result in long vehicles, such as low-bed trailers, getting stuck and risking further fatal accidents. A review and revision of the road's geometry is recommended